Association of cumulative non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio with the risk of cardiometabolic disease - Liu, Luqing; Liu, Shihe; Liao, Yicheng; Zhang, Xiaoxue; Wang, Meixiao; Lin, Liming; Zhu, Chenrui; Wu, Shouling; Wu, Yuntao (Frontiers in Cardiovascular Medicine, 2024)
BackgroundOne measurement of non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) is considered to be associated with insulin resistance and cardiovascular disease (CVD) risk. This study aimed to exploring the association between cumulative non-high-density lipoprotein cholesterol/high-density lipoprotein cholesterol (Cum NHHR) exposure levels and the risk of cardiometabolic disease (CMD).MethodsThis prospective cohort study included 43,735 participants, who participated in three consecutive health examinations in 2006, 2008, 2010 and had no history of CMD or cancer. The participants were divided into quartiles bases on their cum NHHR. Multivariate Cox proportional hazards model was used to assess the association between cum NHHR and the risk of CMD. Additionally, the direct method of standardized ratios was employed to calculate the absolute risk of CMD attributable to cum NHHR.ResultsOver a median follow-up period of 10.92 years (IQR: 10.22–11.26 years), 7,388 participants were newly diagnosed with CMD. In the multivariate-adjusted model, participants in quartiles Q2, Q3 and Q4 showed a progressively increased relative risk of CMD compared to those in Q1, The fully adjusted hazard ratios (95% confidence intervals) for the risk of CMD in the Q2, Q3, and Q4 groups were 1.11 (1.04–1.20), 1.23 (1.14–1.32), and 1.29 (1.20–1.38), respectively, compared with the Q1 group. This association remained significant even after further adjustment for single measurements of NHHR. Moreover, cum NHHR was positively correlated with the absolute risk of CMD, cardiovascular diseases (CVD), and type 2 diabetes (T2DM).ConclusionsHigher cum NHHR is significantly associated with an increased risk of CMD, independent of single-point NHHR level. Additionally, there are significant different strengths of correlations between cum NHHR and different diseases.